Does a Proposition Have Three Parts or Four? A Debate in Later Arabic Logic - El-Rouayheb, Khaled (Oriens, 2016)
The present article traces the controversy on propositions and their parts, intensively discussed by logicians writing in Arabic in the fourteenth, fifteenth and sixteenth centuries. From the beginning of the Arabic logical tradition to the end of the thirteenth century, the dominant view among Arabic logicians was that a categorical proposition consists of three parts: subject, predicate and nexus between them indicated (in most languages) by the copula. A number of influential logicians from the fourteenth century suggested that the parts are strictly four: the subject, the predicate, the nexus between them, and the judgment. This thesis was criticized in the late fifteenth century, most influentially by the Persian scholar Dawānī (d.1502). His criticism and the ensuing discussion came to be intertwined with another controversial issue: can some objects of conception (taṣawwur) also be objects of assent (taṣdīq)?